Design of Microcontroller-Based Portable Instrument for Measuring P-Wave Speed in Impact-Echo Method - Slamet Riyadi; Khairul Anuar Mohd. Nayan; Mohd. Marzuki Mustafa (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
Impact-echo method is widely used for non-destructive testing on concrete evaluation. One of the procedures of this method is determining P-wave speed by measuring travel time of P-wave ( between two transducers. For this purpose, a microcontroller-based portable instrument is developed. This research proposes a PIC microcontroller routine using interrupt-on-change and timer0 features. On concrete, impact waves reach the first accelerometer and will interrupt the main routine and start the timer0. When the waves reach the second accelerometer, the timer0 will be stopped. The value of the timer represents the travel time of P-wave. Therefore, the P-wave speed can be calculated. The routine is verified using controlled signal generated by internal PIC. The accurate result of the travel time measurements is presented. )tΔKeywords: impact-echo, P-wave speed, PIC microcontroller, interrupt-on-change, timer0